Austism Spectrum Disorder and the Brain-Gut-Microbiome Axis - Furland, Natalia Edith (2015)
Background: Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder where a high frequency of gastrointestinal (GI) dysfunction (e.g., constipation, diarrhea, bloating, gas, and history of reflux) is reported. However, the mechanism underlying GI tract defects in autistic children as well as the association between abnormal GI structure and function with ASD is yet to be clearly understood. GABA and serotonin functions as key neurotransmitters at both, the central nervous system and the gastrointestinal tract, and there is accumulating evidence pointing to a critical role for the gut microbiome in regulating normal functioning of tryptophan metabolism and the GABAergic system. There is also substantial overlap between ASD behaviours that could be influenced by the gut microbiota. Objectives: the aim of this work is to analyse and identify differences on fecal microbiota (as a proxy for gut microbiota), some neurotransmitters levels and SCFA (short chain fatty acids) between autistic children and healthy donors. If the unique microbial flora or metabolic profile is found to be a causative or consequent factor in GI disorders in ASD, it may have implications with regard to a specific diagnostic test, its epidemiology, and therapeutic targeting of the gut microbiota as a viable treatment strategy for ASD Methods: we analyzed Serotonin and Dopamine, both neurotransmitter monoamines involved in modulating adult cortical plasticity, also GABA and SCFA (short chain fatty acids) profile in fecal samples in a cohort of 30 patients that met DSM V criteria for autism based on ADOS and their typical developed (TD) siblings. The control sample consisted of 35 healthy donors, sex-matched with the case sample. Results: Autistic patients have a unique microbiome consisting of more clostridial species. Half of all autistic children with gastrointestinal dysfunction were found to have Sutterella, a bacteria which is absent in no autistic children with gastrointestinal dysfunction. Our results show that microbiota and metabolic profiles from ADS children significantly differ from their healthy siblings and controls and suggest a potential correlation with gastrointestinal dysfunction. Conclusions: Differences in microbiota and some metabolites levels found in ADS children stools versus controls correlates with GI distress. Also CNS neurotransmission can be profoundly disturbed by the gut microbiome in ASD